The barriers associated with a sedentary lifestyle in the working population (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2023)
Sedentary behavior and physical inactivity constitute a global health concern associated with a higher incidence of chronic diseases and premature deaths. the rise in obesity, diabetes, and cardiovascular diseases is linked to sedentary behavior, highlighting the urgent need to address this public health issue. despite historical awareness of the detrimental effects of inactivity, approximately one-third of the world's population is inactive today, posing a significant public health problem. over the past 50 years, occupational physical activity has decreased, and sedentary behavior has emerged as an additional risk factor alongside physical inactivity. public health measures have been ineffective in curbing the obesity epidemic over the last three decades, emphasizing the need for a paradigm shift to effectively prevent its escalation. physical inactivity and sedentary behavior each present unique health risks, necessitating separate consideration to explore their distinct harmful mechanisms.
Keywords: Physical inactivity; Sedentariness; Chronic diseases; Sedentary behavior; Office workers